Concentrically loaded slender square hollow and composite columns incorporating high strength properties. (15th January 2017) - Khan, M.; Uy, B.; Tao, Z.; Mashiri, F.
Highlights: Slender welded box and composite sections were investigated. Slender test specimens were fabricated from 690 MPa steel and 113 MPa concrete. Finite element models were developed and verified with the experimental results. Current design buckling curves were investigated with the results. Abstract: This paper presents an experimental investigation of longitudinally slender box sections (HS) having compact and non-compact cross-sections as well as slender composite sections (CB) fabricated from high strength steel (HSS) and high strength concrete (HSC). Fifteen test specimens (HS) and thirty nine test specimens (CB) having width to thickness ratios ( b / t ) ranging from 15 to 40 and slenderness ratios ranging from 18 to 124 were tested to failure. Finite element modelling (FEM) of the test specimens (HS and CB) was verified with the experimental results for further analysis. The FEM was used to investigate the effects of residual stresses induced from lightly and heavily welded box sections on the member capacity of slender box sections. The column curves of various design specifications pertaining to slender welded box sections were reviewed by the experimental and FEM peak strengths for the purpose of selecting the most appropriate curves for non-compact box sections. Likewise, the column curves pertaining to the slender composite sections were reviewed by the experimental and FEM peak strengths for the purpose of selecting the most appropriate curves for high strength composite columns fabricated from HSS (690 MPa) and HSC (80–130 MPa).